Early Eocene clinoenstatite boninite and boninite-series dikes of the ophiolite of New Caledonia; a witness of slab-derived enrichment of the mantle wedge in a nascent volcanic arc - Cluzel, D.; Ulrich, M.; Jourdan, Fred; Meffre, S.; Paquette, J.; Audet, M.; Secchiari, A.; Maurizot, P. (Elsevier BV, 2016)
© 2016 Elsevier B.V.Clinoenstatite-bearing boninites (CE-boninite) from the serpentinite sole of the Cenozoic ophiolite of New Caledonia near Nepoui have been dated by the 40Ar/39Ar method, yielding two plateau ages of 47.4±0.9Ma and 50.4±1.3Ma. Coarser grained, geochemically similar boninite-series felsic dikes consistently yielded U-Pb zircon ages of ca. 54Ma.Nepoui CE-boninites display whole rock geochemical features similar to that of Cape Vogel boninites (Papua-New Guinea). They similarly have been generated by low degree hydrous melting of depleted peridotite. High contents in LILE and LREE, and some elemental ratios suggest source enrichment by subduction-derived fluids and melts. However, unlike the Cape Vogel boninite, moderately depleted MORB-like isotopic signatures (eNd50 =7.9) rule out the role of OIB-like, or E-MORB component that might account for the relatively high LREE and LILE contents measured in the rocks. Nd isotopic ratios and positive anomalies in Zr and Hf are closely similar to that of the slightly older felsic dikes (55-50Ma) that crosscut the peridotite from the ophiolite in New Caledonia. Most of these magmas have been generated by slab melting during the early stages of intra-oceanic subduction. The Early Eocene subduction started at or near the "oceanic" ridge and involved young and hot lithosphere; therefore, slab-derived melts may have reacted locally with hot depleted peridotites. Finally, water influx into the mantle wedge during the subduction of slightly older (cooler and hydrated) lithosphere initiated a low degree partial melting event in the mantle wedge and generated the CE-boninite magma.Geochemical modeling of hydrous melting of a depleted mantle re-enriched by slab melts suggest that the additional slab melt component was derived from the partial melting of a BABB-like barroisite-bearing eclogite, similar to some elements of the Eocene HP-LT Pouebo terrane. This potential magma source is similar to the BABB-like HT amphibolites of the metamorphic sole of the ophiolite, which have the same origin. Geochemical modeling also suggests that CE-boninite magma may have been in equilibrium with the enstatite-bearing gabbro cumulates that crop out in several places of the Massif du Sud.However, modeling fails in establishing that harzburgite of the same massif simply corresponds to the melting residue of this process. It appears that ultra-depleted supra-subduction peridotites of the Massif du Sud are probably not directly related to the overlying gabbro cumulates.